Experimental discrimination between charge 2e/3 top quark and charge 4e/3 exotic quark production scenarios - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We present the first experimental discrimination between the 2e/3 and 4e/3 top quark electric charge scenarios, using top quark pairs (tt̄) produced in pp̄ collisions at s=1.96TeV by the Fermilab Tevatron Collider. We use 370pb-1 of data collected by the D0 experiment and select events with at least one high transverse momentum electron or muon, high transverse energy imbalance, and four or more jets. We discriminate between b- and b̄-quark jets by using the charge and momenta of tracks within the jet cones. The data are consistent with the expected electric charge, |q|=2e/3. We exclude, at the 92% C.L., that the sample is solely due to the production of exotic quark pairs QQ̄ with |q|=4e/3. We place an upper limit on the fraction of QQ̄ pairs ρ<0.80 at the 90% C.L. © 2007 The American Physical Society.